Undulating periodization models for strength training & conditioning - A. Jiménez (Desafio Singular, 2009)
Periodized strength training refers to varying the training program at regular time intervals in an attempt to bring about optimal resistance gains. The main aim of this paper was to present a short review of the diferent aspects of training periodization and its effects with performance. as well as the differential effect of alternate periodization models on other populations, and specially the need for further research regarding the effectiveness of the undulating model as compared with the linear model. A focussed literature review reveals that most studies that examined strength training periodization utilized young males as their subject population, and the research has mainly focused on differences between periodized and non-periodized programs. Furthermore, the periodization training programs are designed and developed according to two different models: the linear model and the non-linear model. The Linear Model is characterized by high initial training volume and low and intensity. The Non-Linear Model enables variation in intensity and volume within each 7-10 day cycle by rotating different protocols to train various components of the neuromuscular system. The results showed at the scientific literature encourage researchers and exercise professionals to include non-linear (undulating) periodization models during resistance training.